2020
DOI: 10.1111/ajt.15793
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of CMV-specific cell-mediated immunity with a commercial ELISA-based interferon-γ release assay in kidney transplant recipients treated with antithymocyte globulin

Abstract: Monitoring for cytomegalovirus (CMV)-specific cell-mediated immunity (CMV-CMI) may be useful for individualizing valganciclovir (VGCV) prophylaxis after kidney transplantation (KT). We performed a commercial ELISA-based interferon (IFN)-γ release assay (QTF-CMV) from posttransplant months 2-5 (362 points) in 120 CMVseropositive KT recipients that received antithymocyte globulin as induction therapy and VGCV prophylaxis (median of 92 days). Forty-seven patients (39.3%) had CMV infection after discontinuation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
0
31
0
4
Order By: Relevance
“…IFN-γ was detected by ELISA and the measured optical density was converted to IFN-γ concentration (IU/mL) using ELISA Report Software (SD Biosensor). Because the positive cut-off value of the SARS-CoV-2 IGRA kit had not been established, IFN-γ concentration of the Sp tubes minus that of the Nil tube was compared quantitatively between the groups, and a tentative cut-off values were applied: mean + 3 standard deviations (SDs) of IFN-γ concentration of the Nil tubes (0.84 IU/mL), which is higher than that used in previous IGRAs for tuberculosis (0.35 IU/mL) or CMV (0.2 IU/mL) ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…IFN-γ was detected by ELISA and the measured optical density was converted to IFN-γ concentration (IU/mL) using ELISA Report Software (SD Biosensor). Because the positive cut-off value of the SARS-CoV-2 IGRA kit had not been established, IFN-γ concentration of the Sp tubes minus that of the Nil tube was compared quantitatively between the groups, and a tentative cut-off values were applied: mean + 3 standard deviations (SDs) of IFN-γ concentration of the Nil tubes (0.84 IU/mL), which is higher than that used in previous IGRAs for tuberculosis (0.35 IU/mL) or CMV (0.2 IU/mL) ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that the QuantiFERON-CMV assay before and 1 month after immunosuppression had suboptimal accuracy for predicting protective CMV-specific CMI (sensitivity, 77.4%; specificity, 34.3%; positive predictive value, 64.1%; and negative predictive value, 50.0%); there was a nonsignificant difference in 1-year CMV infection rates between QF− (nonreactive or indeterminate) and QF+ patients [ 33 ]. A few previous studies suggested a modified cutoff value (≥0.1 IU/mL) to increase the test’s sensitivity for immunocompromised patients, particularly CMV-seropositive SOT recipients [ 33 , 34 ]. We were able to distinguish those at risk of CMV infection by using the cutoff value suggested by the manufacturer 1 month postimmunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies have found a clear association between CMV-CMI and protection against future CMV infection. Recently, Fernandez-Ruiz et al reported on the assessment of CMV-CMI using QFN-CMV at EOP in R+ kidney transplant recipients receiving rATG induction [ 79 ]. Their data demonstrated suboptimal accuracy for predicting 1-year CMV infection rates (45.8% in persons with non-reactive or indeterminate results vs. 36.1% in persons with reactive results, p = 0.244).…”
Section: Clinical Utility Of CMV Cell-mediated Immunity (Cmi) Assaysmentioning
confidence: 99%